Cardioprotective Agents for the Primary Prevention of Trastuzumab-Associated Cardiotoxicity: A Systematic Review and Meta-Analysis - Kyriakos Goulas; Dimitrios Farmakis; Anastasia Constantinidou; Nikolaos P. E. Kadoglou (MDPI AG, 2023)
There are significant considerations about the prevention of cardiotoxicity caused by trastuzumab therapy in patients with breast cancer, leading to discontinuation. Recently, randomized controlled trials (RCTs) have evaluated the effects of early commitment of beta-blockers (BBs), angiotensin receptor blockers (ARBs) and angiotensin converting enzyme inhibitors (ACEIs) during trastuzumab chemotherapy in order to prevent the related cardiotoxicity. The present systematic review and meta-analysis of six RCTs included patients who have predominantly non-metastatic, HER2-positive, breast cancer and received trastuzumab as primary or adjuvant therapy. Those patients did not have any obvious cardiac dysfunction or any previous therapy with cardioprotective agent. We evaluated the efficacy of the aforementioned medications for primary prevention of cardiotoxicity, using random effects models. Any preventive treatment did not reduce cardiotoxicity occurrence compared to controls (Odds ratios (OR) = 0.92, 95% CI 0.54-1.56, p = 0.75). Results were similar for ACEIs/ARBs and beta-blockers. Treatment with ACEIs/ARBs led to a slight, but significant, increase in LVEF in patients compared to the placebo group. Only two studies reported less likelihood of discontinuation of trastuzumab treatment. More adequately powered RCTs are needed to determine the efficacy of routine prophylactic therapy.